OP0191 EPIGENETIC PROFILING OF SYNOVIAL FIBROBLASTS REVEALS STRUCTURAL DNA DYNAMICS AT DISEASE IMPLICATED CHROMOSOME REGIONS. (June 2019) - Ge, Xiangyu; Frank-Bertoncelj, Mojca; Mcgovern, Amanda; Orozco, Gisela; Martin, Paul; Ospelt, Caroline; Eyre, Stephen
Abstract : Background: One of the more striking findings from genome-wide association studies (GWAS) is how the majority of disease associated genetic variants are found within gene regulatory regions, known as enhancers. It is now well established that these enhancers regulate target genes through physical interactions. We, and others, have shown that these interactions can vary between cell types and act over long distances. Therefore, if we are to fully translate GWAS findings, we need link disease associated enhancers to their target genes, in the relevant cell types. So far we only have a limited picture in rheumatoid arthritis (RA) relevant cell types, since synovial fibroblasts (SF) have been omitted from this type of chromatin interaction analysis. Objectives: Investigate dynamic Hi-C interactions in unstimulated and stimulated SF, mapping RA enhancers to their target genes, and correlating with gene expression. Methods: We cultured SF from synovial tissues of RA patients. After stimulation of the SF (n=6) with 10 ng/ul TNF for 24h, Hi-C and RNA libraries were generated and sequenced on the Illumina HiSeq 4000. We called dynamic active and inactive regions of the genome (A/B compartments), mapped on RA associated enhancers, linked these to target genes and correlated the interactions with dynamic expression. Results: We found a region on the chromosome 6q23, intergenic between OLIG3 and TNFAIP3, with an enhancer containing SNPs associated with RA to be dynamically linked to the TNFAIP3 gene through DNA activity, interactions and corresponding gene expression. As shown in figure 1a, the genomic region containing the RA associated variants (red square) only resides in an open, active region of DNA (black bar, compartment A) upon TNF-stimulation of the SF. This region then makes a strong interaction with the promoter of TNFAIP3 (figure 1a) in stimulated cells, which corresponds to a more than 100-fold increase in TNFAIP3 gene expression (figure 1b). Conclusion: Using independent data, we have indicated how the RA region on 6q23 could influence the expression of TNFAIP3, under stimulatory conditions in SF cells. This supports previous work, where this particular 6q23 enhancer is preferentially active in RA synovium, compared to osteoarthritis, reflecting the different stimulatory conditions in each disease (Ai et al. 2018 ). We have successfully linked an RA associated enhancer to its target gene in SF, indicating how the enhancer works over a large distance to interact with and regulate the TNFAIP3 gene. Furthermore we show that this enhancer containing RA associated SNPs is only active upon stimulation with TNF in SF. Reference: [1] Ai R, et al. Nat Commun. 2018 May 15;9(1):1921 Disclosure of Interests: None declared